(3JMHjQ GdehTjf aj GdJYHjQ HGdSjf hGdTjfs - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , MeOkG jSJhLH bGFdg GdEMSGf hGdJMSjf hHYO , jbhd gPG GdcJGH SHH JCdjag Cfi bQCJ Ydi HYV eTjNJi LRA MOjK LQi ajg PcQ GdJTejJ , afWbJ ajgG HGdSjf hGdTjf s
(3BNQgG (B:s
(3jbGd gGS jgjS gjSkG , hjbGd gGT GdCQV jgjTgG Ci jObgG GdjGA jhSY hjhTY aJi ehSi YdjgeG GdSdGe bGd GdHNGQi jfWb ajgG HGdSjf hGdTjf hGddg GYde Je cJGH JMHjQ GdehTjf HGdJYHjQ HGdSjf hGdTjf s
(3HgG fXGe GdJYbjHIs
(3ai cTa GdXfhf GdeNWhW gh JMHjQ GdehTjf ai eG jbGd HGdSjf hGdTjf hcPdc ai GdCYdGes
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs